American Grand Strategy in Africa: From Hegemony to the Balance of Power? - Amina, M’lili (The Journal of US Africa -Studies, 2023)
This paper explores the American grand strategy in Africa; more specifically in response to economic and security issues and socio-political instability in different regions of Africa. Having said that, this paper does not seek to re/appraise the US economic areas or/and security role and/or strategies to avert and halt the widespread terrorism in different parts of the African Continent. Instead, it explores the American grand strategy in Africa from a theoretical perspective. To capture this argument, the study uses Kenneth Waltz’s theory of Balance of Power (1979) as the most advanced theoretical framework to illustrate that the United States, as a great power, is power balancing China’s and Russia’s expanding geopolitical influence in Africa through military and economic cooperation. The paper argues that the United States’ goal behind power balancing with China and Russia is to make sure that their presence is not used to turn the African continent into the Eastern sphere of influence. The theoretical contribution of this research paper is to expand the understanding of Kenneth Waltz’s Balance of Power theory; especially balance by engaging in the competitive acquisition of territory and forming alliances. Keywords: The Theory of Balance of Power, American Grand Strategy, Africa, Hegemony, China, Russia.